2017
DOI: 10.1186/s12872-017-0495-4
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the impact of financial barriers on secondary prevention of heart disease

Abstract: BackgroundPatients with coronary artery disease experience various barriers which impact their ability to optimally manage their condition. Financial barriers may result in cost related non-adherence to medical therapies and recommendations, impacting patient health outcomes. Patient experiences regarding financial barriers remain poorly understood. Therefore, we used qualitative methods to explore the experience of financial barriers to care among patients with heart disease.MethodsWe conducted a qualitative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
2
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 38 publications
1
25
2
1
Order By: Relevance
“…It was particularly interesting to see that the paid membership was rated as the most helpful strategy. This is consistent with the literature reporting that access (e.g., finances, transportation, inclement weather) is a common barrier to routine exercise in HF patients (Barbour & Miller, ; Conraads et al, ; Cooper et al, ; Dhaliwal et al, ). The HR monitor, setting goals, education classes and coaching were all very close in ratings of helpfulness (8.43–8.82 on a 10‐point scale).…”
Section: Discussionsupporting
confidence: 91%
“…It was particularly interesting to see that the paid membership was rated as the most helpful strategy. This is consistent with the literature reporting that access (e.g., finances, transportation, inclement weather) is a common barrier to routine exercise in HF patients (Barbour & Miller, ; Conraads et al, ; Cooper et al, ; Dhaliwal et al, ). The HR monitor, setting goals, education classes and coaching were all very close in ratings of helpfulness (8.43–8.82 on a 10‐point scale).…”
Section: Discussionsupporting
confidence: 91%
“…11 Further, inadequate prescriptions (20.2%), financial issues (15.5%), medication cost, social stigma, and family support have been associated with improved medication adherence in patients with heart failure. 3,[24][25][26][27] Health system factors Few patients reported that unavailability of medication or a requirement for lifestyle changes resulted in nonadherence. However, with the lack of public health facilities and infrastructure in the country, along with the considerable number of complaints regarding the health service, one would expect these factors to contribute to non-adherence.…”
Section: Social Cultural and Economic Factorsmentioning
confidence: 99%
“…The high cost of medications is frequently cited by CAD patients as a major driver of non-adherence [30, 31]. This likely explains why prescription drug coverage has previously and, in recent literature, continues to be positively associated with medication adherence.…”
Section: Socioeconomic Factorsmentioning
confidence: 99%